2003
DOI: 10.1083/jcb.200210166
|View full text |Cite
|
Sign up to set email alerts
|

deep-orange and carnation define distinct stages in late endosomal biogenesis in Drosophila melanogaster

Abstract: Endosomal degradation is severely impaired in primary hemocytes from larvae of eye color mutants of Drosophila. Using high resolution imaging and immunofluorescence microscopy in these cells, products of eye color genes, deep-orange (dor) and carnation (car), are localized to large multivesicular Rab7-positive late endosomes containing Golgi-derived enzymes. These structures mature into small sized Dor-negative, Car-positive structures, which subsequently fuse to form tubular lysosomes. Defective endosomal deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
124
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(139 citation statements)
references
References 49 publications
14
124
1
Order By: Relevance
“…The merged early endosomes containing Wg and DFz2 (10-15 min) in the wing disc are also positive for Rab5 GFP (Fig. S1 F-H), an early endosomal marker (28,29). Hence, these endosomes probably act as sites of colocalization and concentration of Wg and DFz2, even in regions where their surface concentrations are low.…”
Section: Resultsmentioning
confidence: 95%
“…The merged early endosomes containing Wg and DFz2 (10-15 min) in the wing disc are also positive for Rab5 GFP (Fig. S1 F-H), an early endosomal marker (28,29). Hence, these endosomes probably act as sites of colocalization and concentration of Wg and DFz2, even in regions where their surface concentrations are low.…”
Section: Resultsmentioning
confidence: 95%
“…We further observed that RLVs label with GFP-tagged Rab7 (Entchev et al, 2000) (Fig. 2B), an endosomal protein that marks the limiting membrane of MVBs in Drosophila (Sriram et al, 2003) and other systems (Raiborg et al, 2003). RLVs also immunostain for Hrs (Fig.…”
Section: Rlvs Are Mvbsmentioning
confidence: 94%
“…The Vps33b-VIPAR-Rab11a complex associates with recycling endosomes and functions in the apical delivery of membrane proteins in polarized cells of humans, mice and zebrafish 42 (and unpublished data of the Klumperman and Gissen labs). Moreover, in yeast and Drosophila, mutations in the core class-C proteins give distinct phenotypes, suggesting that individual subunits have distinct activities 29,39 . Thus, specific HOPS components might function in multiple complexes, located at distinct membranes and mediating separate pathways.…”
Section: Articlementioning
confidence: 99%